The moderating role of work involvement in influencing the relationship between person-environment fit and organizational citizenship behaviour among public service employees / Ayu Kamareena Abdullah Thani and Abdul Kadir Othman - Abdullah Thani, Ayu Kamareena; Othman, Abdul Kadir (Faculty of Business and Management, Universiti Teknologi MARA, Shah Alam, Malaysia, 2018)
Studies have put considerable effort to examine the influence of personenvironment fit on organizational citizenship behaviour (OCB). However, the findings indicate that the direct relationship is not always satisfactory. Therefore, this study decided to introduce work involvement as a moderator to clearly explained the influence of person-environment fit and OCB. A total of 376 questionnaires were distributed and 371 questionnaires were returned, giving a response rate of 98.67%. The SPSS was used for the analysis. Person-environment fit consists of person-job fit, person-organization fit, person-group fit and person-supervisor fit. The results of this study show that work involvement moderates the relationships between person-job fit and OCB, person-organization fit and OCB and person-supervisor fit and OCB. The implications of the study are discussed in the paper.